Carbon Trading and Environmental Justice: A Juridical Examination of Fairness in Indonesia's Emissions Reduction Initiative - Rahmawati, Diah Ayu; Haryono, Haryono; Endarto, Budi; Soraya, Joice; Ngaisah, Siti (West Science Law and Human Rights, 2024)
This paper provides a normative juridical analysis of Indonesia's carbon trading regulations, with a focus on environmental justice and fairness. It examines the legal framework established by Presidential Regulation No. 98 of 2021, which governs carbon pricing mechanisms, including carbon taxes and carbon credit trading. The analysis highlights key gaps in the regulation, particularly in terms of equitable benefit distribution and inclusion of vulnerable communities in decision-making processes. While Indonesia's carbon trading system aligns with global trends and its international obligations, significant improvements are needed to ensure that marginalized groups are not further disadvantaged. Recommendations include the redistribution of carbon trading revenues, enhanced public participation, stronger enforcement mechanisms, and alignment with international best practices.